The impact of geriatric focused nurse assessment and intervention in the emergency department: A systematic review. (March 2018) - Malik, M.; Moore, Z.; Patton, D.; O'Connor, T.; Nugent, L.E.
Highlights: Nursing focused assessment and interventions did not impact hospital utilization. Risk screening patients in ED did not yield positive outcomes. More research is needed to assess risk screening, intervention and follow-up. Abstract: Background: Nursing assessment of elderly patients is imperative in Emergency Departments (ED) while providing interventions that increase independence facilitating discharge to primary healthcare. Aims: To systematically review the impact of geriatric focused nurse assessment and intervention in the ED on hospital utilisation in terms of admission rate, ED revisits and length of hospital stay (LOHS). Methods: Search strategy used following databases; Cochrane, Medline, CINAHL, Embase, Scopus and Web of Knowledge; And terms; geriatric nurse assessment, nurse discharge planning, geriatric nurse specialist, nurse intervention, emergency department, accident and emergency, patient outcomes, discharge, admissions, readmissions, hospital utilization, hospitalization, length of stay/hospital stay. Results: Nine studies were included: seven RCTs and two prospective pre/post-intervention designed studies. Geriatric focused nursing assessment and interventions did not have a statistical impact on hospitalization, readmissions, LOHS and ED revisits. Risk screening and comprehensive geriatric assessment extending into primary care may reduce readmission rates but not affect hospitalization. An increase in ED visits in the intervention group at 30 days post-intervention was noted. Conclusion: Inconsistencies in assessment and interventions for the older person in ED are apparent. Further research evaluating a standardised risk assessment tool and innovative interventions extending into primary healthcare is required.